A polo-like kinase modulates cytokinesis and flagella biogenesis in Giardia lamblia - Park, Eun-Ah (Parasit Vectors, 2021)
BACKGROUND: Polo-like kinases (PLKs) are conserved serine/threonine kinases that regulate the cell cycle. To date, the role of Giardia lamblia PLK (GlPLK) in cells has not been studied. Here, we report our investigation on the function of GlPLK to provide insight into the role of this PKL in Giardia cell division, especially during cytokinesis and flagella formation. METHODS: To assess the function of GIPLK, Giardia trophozoites were treated with the PLK-specific inhibitor GW843286X (GW). Using a putative open reading frame for the PLK identified in the Giardia genomic database, we generated a transgenic Giardia expressing hemagglutinin (HA)-tagged GlPLK and used this transgenic for immunofluorescence assays (IFAs). GlPLK expression was knocked down using an anti-glplk morpholino to observe its effect on the number of nuclei number and length of flagella. Giardia cells ectopically expressing truncated GlPLKs, kinase domain + linker (GlPLK-KDL) or polo-box domains (GlPLK-PBD) were constructed for IFAs. Mutant GlPLKs at Lys51, Thr179 and Thr183 were generated by site-directed mutagenesis and then used for the kinase assay. To elucidate the role of phosphorylated GlPLK, the phosphorylation residues were mutated and expressed in Giardia trophozoites RESULTS: After incubating trophozoites with 5 μM GW, the percentage of cells with > 4 nuclei and longer caudal and anterior flagella increased. IFAs indicated that GlPLK was localized to basal bodies and flagella and was present at mitotic spindles in dividing cells. Morpholino-mediated GlPLK knockdown resulted in the same phenotypes as those observed in GW-treated cells. In contrast to Giardia expressing GlPLK-PBD, Giardia expressing GlPLK-KDL was defective in terms of GIPLK localization to mitotic spindles and had altered localization of the basal bodies in dividing cells. Kinase assays using mutant recombinant GlPLKs indicated that mutation at Lys51 or at both Thr179 and Thr183 resulted in loss of kinase activity. Giardia expressing these mutant GlPLKs also demonstrated defects in cell growth, cytokinesis and flagella formation. CONCLUSIONS: These data indicate that GlPLK plays a role in Giardia cell division, especially during cytokinesis, and that it is also involved in flagella formation. [Image: see text] SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s13071-021-04687-5.